Los decretos ejecutivos 238 y 239 y su incidencia en los principios constitucionales de no discriminación y seguridad jurídica - Arguello Toromoreno, Jaime Servando (2023)
The Constitution of the Republic of Ecuador, in its article 147, paragraph 3, establishes the power of the Constitutional President of the Republic to define and direct the public policies of the Executive Function. Under that premise, on October 26, 2021, Executive Decree No. 238 was issued, which establishes the Policies for the Electricity Sector. Additionally and on the same date, it issued Executive Decree No. 239, which contains various reforms to the Regulations of the Organic Law of the Public Electric Energy Service. When reviewing and contrasting such policies and regulatory reforms against the specialty law, the main problem lies in how, under motivational deficiencies, benefits are established and the contractual nature of self-generating companies is changed, equating them with pure generating companies, who, to qualify as such and obtain their concession contract, they met greater and demanding requirements. Through constitutional analysis, the aforementioned aspects show a violation of the latter's legitimate right to participate in the Ecuadorian electricity sector, under a supposed legal security, attraction of private investment and development of public companies, unmotivatedly granting a supposed equality of conditions and preferences that are legally, regulatory and contractually lacking. The non-observance of constitutional principles, as well as the established legal parameters, causes an operational and therefore economic impact on the generating companies and the State itself, which results in the need for an abstract control of constitutionality, safeguarding the fundamental elements of the Right.